Visitor

2015-11-30 04:50:43

#1

How to solve this?

z(z^{2} + z + 1)(z^{2} + 25) = 0

z(z

Visitor

2015-12-04 04:18:16

#2

Here you can split your equation in three equations. There we have a product which is equal with 0. So though, every factor of this product could be zero.

So though,

**Sol. 1.** z = 0 ..

And this is one of the solutions.

**Sol. 2.** z^{2} + z+ 1 = 0

This is a two degree equation. So, we have to find out the Discriminant,

Δ = 1 - 4 = -3 < 0 => the equation doesn't have real solutions

**Sol. 3.** z^{2} + 25 = 0

The same as above. This is a two degree equation. So, we have to find out the Discriminant,

Δ = 0 - 25 = -25 < 0 => the equation doesn't have real solutions

**Finally**, the entire equation has only one solution: 0

So though,

And this is one of the solutions.

This is a two degree equation. So, we have to find out the Discriminant,

Δ = 1 - 4 = -3 < 0 => the equation doesn't have real solutions

The same as above. This is a two degree equation. So, we have to find out the Discriminant,

Δ = 0 - 25 = -25 < 0 => the equation doesn't have real solutions

It is not mandatory to be logged in on this forum but it is nice to have an account. You can ask about mathematics just with your name and your email.

This maths forum is one of the easiest forums to use it.